PENINGKATKAN KESELAMATAN PELAYARAN DI KOTA BATAM MENGGUNAKAN LOGIKA FUZZY - Sestri Novia Rizki; Handra Tipa (Universitas Putera Batam, 2019)
At present, many accidents occur on shipping, whether from human negligence or from disasters that occur without human knowledge. Then a rule is made before sailing the parties concerned must check everything related to shipping to avoid accidents. Batam is an archipelago that is connected between many islands, so that sea transportation is the main budget in crossing to various islands. Nowadays there are many accidents such as ships sinking, ships colliding and ships burning, this is due to human negligence. The main objective of this research is to improve shipping safety in Batam City, by observing the waves and engine checks when the ship is about to depart the crew must pay attention to this in order to avoid accidents on the cruise that will be used. So that the passenger safety of the ship is guaranteed. In this study using the mamdani method. The Mamdani method looks for the smallest value to the greatest value. In the Fuzzy method there are three operators, OR, AND and NOT operators. This study uses the OR operator. The steps of this research work, 1. Determine the input variable 2, determine the fuzzy set, 3, rule composition, 4, the final result is in the form of defuzification. The results of this study are in the form of a decision-making system in determining the level of maritime shipments and how to prevent them from occurring accidents in the shipping system by taking into account the input variables that have been set such as safety devices, paying attention to waves and always checking ship engines regularly. So that accidents can be avoided. So that the safety of shipping in the city of Batam is more guaranteed.